Novel Extracellular Electron Transfer Channels in a Gram-Positive Thermophilic Bacterium - Gavrilov, Sergey N.; Zavarzina, Daria G.; Elizarov, Ivan M.; Tikhonova, Tamara V.; Dergousova, Natalia I.; Popov, Vladimir O.; Lloyd, Jonathan R.; Knight, David; El-Naggar, Mohamed Y.; Pirbadian, Sahand; Leung, Kar Man; Robb, Frank T.; et al. (Frontiers in Microbiology, 2021)
Biogenic transformation of Fe minerals, associated with extracellular electron transfer (EET), allows microorganisms to exploit high-potential refractory electron acceptors for energy generation. EET-capable thermophiles are dominated by hyperthermophilic archaea and Gram-positive bacteria. Information on their EET pathways is sparse. Here, we describe EET channels in the thermophilic Gram-positive bacterium Carboxydothermus ferrireducens that drive exoelectrogenesis and rapid conversion of amorphous mineral ferrihydrite to large magnetite crystals. Microscopic studies indicated biocontrolled formation of unusual formicary-like ultrastructure of the magnetite crystals and revealed active colonization of anodes in bioelectrochemical systems by C. ferrireducens. The internal structure of micron-scale biogenic magnetite crystals is reported for the first time. Genome analysis and expression profiling revealed three constitutive c-type multiheme cytochromes involved in electron exchange with ferrihydrite or an anode, sharing insignificant homology with previously described EET-related cytochromes thus representing novel determinants of EET. Our studies identify these cytochromes as extracellular and reveal potentially novel mechanisms of cell-to-mineral interactions in thermal environments.